The "Coase Theorem": A Reexamination - Mumey, G. A. (Quarterly Journal of Economics, 1971)
Bargaining and threat making, 719. — Internal cum external costs, 720. — Indifference of liability placement versus no-liability law, 721. — Summary, 723.